Adolescent experiences, perceptions, and preferences for the process of HIV status disclosure in Kenya - Mugo, Cyrus; Njuguna, Irene N.; Beima-Sofie, Kristin; Mburu, Caren W.; Onyango, Alvin; Itindi, Janet; Richardson, Barbra A.; Oyiengo, Laura; John-Stewart, Grace; Wamalwa, Dalton C. (Frontiers in Public Health, 2023)
Introduction Disclosure of HIV status to adolescents living with HIV has been associated with improved treatment outcomes. However, there are limited data regarding the experiences of, perceptions of, and preferences for the process of disclosure of HIV status among adolescents and young adults living with HIV (AYLH), especially in sub-Saharan Africa. Methods Young adults living with HIV from 20 HIV clinics in Kenya who participated in a clinical trial evaluating the effectiveness of a disclosure and transition package completed an anonymous survey in 2019. We described their experiences and preferences using counts and proportions and assessed factors associated with satisfaction with the disclosure process using linear regression, reporting age-adjusted mean differences (aMD), and 95% confidence intervals (95%CIs). Results Of the 375 enrolled AYLH, 265 (71%) had perinatally acquired HIV, of whom 162 (61%) were female. The median age of the enrolled AYLH was 16 years (IQR: 14–19 years), and all of them were on antiretroviral therapy (ART). For over half (55%) of the participants, caregivers disclosed their HIV status, and 57% preferred that their caregivers disclose the status to them. Most (78%) of the participants preferred full disclosure by 12 years of age. The majority (69%) believed the disclosure was planned, and 11% suspected being HIV positive before the disclosure. Overall, 198 (75%) AYLH reported that they were ready for disclosure when it happened, and 86% were satisfied with the process. During both pre-disclosure (67 and 70%, respectively) and post-disclosure (>75% for each), AYLH felt supported by the clinic and caregivers. Factors associated with higher satisfaction with the disclosure process were pre-disclosure clinic support (aMD: 0.19 [95%CI: 0.05–0.33]) and pre-disclosure (aMD: 0.19 [0.06–0.31]) and post-disclosure (aMD: 0.17 [0.03–0.31]) caregiver support. AYLH who suspected they were HIV positive before they were disclosed to tended to have lower satisfaction when compared to those who never suspected (aMD: −0.37 [−0.74-(−0.01)]). Overall, they reported that disclosure positively influenced their ART adherence (78%), clinic attendance (45%), and communication with caregivers (20%), and 40% reported being happier after disclosure. Conclusion Young adults living with HIV advocated for an appropriately timed disclosure process with the involvement of caregivers and healthcare workers (HCWs). Support from caregivers and HCWs before and during disclosure is key to improving their disclosure experience.